(3GdSjQI GdfHhjIs - (3XgjQ GdOjf Ydj Hf eMeO Hf eMehO GdcGRQhfj GdHZOGOj, GdcGRQhfj,J (B697 (3g` s
(3ChdgG (B:s
(3Ghdg eHJhQ hChd GdehLhO efg (B: (3GdQLGd jJMOKhf ai GdHjJ HYO GdWYGe aNQL QShd Gddg Udi Gddg Ydjg hSde , hGJHYJg , aLYd jJHY MLQ fSGFg ajSde Ydjgf s
(3BNQgG (B:s
(3GNQg eHJhQ hGNQ GdehLhO efg (B: (3QKGA MSGf Hf KGHJ ddQShd HQhGjI GdScQi Yf GHf MHjH hSHb Pdc PcQ hbJ Oafg Udi Gddg Ydjg hSde s
(3GdfSNI HgG MhGTs
(3Ydi MhGTjgG JUMjMGJ hJYdjbGJs
(3cJHJ GdYfGhjf HGdMeQI s
(3HChdg agQSJ ddehVhYGJ cJHJ HGdMeQI CjVkG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B334s
Keywords: (3GdJGQjNs